A model of chronic enthesitis and new bone formation characterized by multimodal imaging - Czegley, Christine; Gillmann, Clarissa; Schauer, Christine; Seyler, Lisa; Reinwald, Christiane; Hahn, Madelaine; Uder, Michael; Jochmann, Katja; Naschberger, Elisabeth; Stock, Michael; Schett, Georg; Bäuerle, Tobias; et al. (Disease Models & Mechanisms, 2018)
Enthesitis is a key feature of several different rheumatic diseases. Its pathophysiology is only partially known due to the lack of access to human tissue and the shortage of solid animal models for enthesitis. Here we aimed to develop a model, which mimics the effector phase of enthesitis and reliably leads to inflammation and new bone formation.Enthesitis was induced by local injection of monosodium urate crystals (MSU) into the metatarsal entheses of wild type (WT) or oxidative burst-deficient Ncf1** mice. Quantitative variables of inflammation (edema, swelling) and vascularization (tissue perfusion) were assessed by MRI, bone forming-activity by [18F]-fluoride-PET and destruction of cortical bone and new bone formation by CT. Non-invasive imaging was validated by histochemical and histomorphometric analysis.While injection of MSU crystals into WT mice triggered transient mild enthesitis with no new bone formation, Ncf1** mice developed chronic enthesitis accompanied by massive enthesiophytes. In MRI, inflammation and blood flow in the entheses were chronically increased while PET/CT showed osteoproliferation with enthesiophyte formation. Histochemical analyses showed chronic inflammation, increased vascularization, osteoclast differentiation and bone deposition in the affected entheseal sites.Herein we describe a fast and reliable effector model of chronic enthesitis, which is characterized by a combination of inflammation, vascularization and new bone formation. This model will help to disentangle the molecular pathways involved in the effector phase of enthesitis.
EVALuna2:34481